Effects of land-use and tsetse fly control on bird species richness in southwestern Ethiopia - Wilson, C.J.; Reid, Robin S.; Stanton, N.L.; Perry, Brian D. (Wiley, 1997)
Successful control of tsetse (Glossina spp.)-transmitted trypanosomiasis in the Ghibe Valley, Ethiopia, appears to have accelerated conversion of wooded grassland into cropland. Land conversion, in turn, may have fragmented wildlife habitat. The objective of this paper was to assess the influence of the expansion of agricultural land-use, brought about by tsetse control, on ecological properties by using bird species richness and composition as indicators of environmental impacts. Bird species richness and composition (using Timed-Species counts) and habitat structure (using field sampling and remote sensing) were sampled in four land cover/land-use types in areas subjected to tsetse fly control and adjacent areas without control. At the height of the growing season bird species numbers and vegetative complexity were greater in the small-holder, oxen plowed field and riparian woodlands than in wooded grasslands or in large-holder, tractor-plowed fields. Species composition was highly dissimilar (40-70 percent dissimilarity) comparing among land-use types, with many species found only in a single type. This implies that trypanosomiasis control that results in land conversion from wooded grasslands to small-holder farming in this region may have no adverse impacts on bird species numbers but will alter composition. These results also suggest that moderate land-use by humans (e.g., small-holder field mosaics) increases habitat heterogeneity and bird species richness relative to high levels of use (e.g., tractor-plowed fields). Tsetse control may be indirectly maintaining species richness in the valley by encouraging the differential spread of these small-scale, heterogeneous farms in place of large-scale, homogeneous farms. Nevertheless, if the extent of small-holder farms significantly exceeds that of present levels, negative impacts on bird species richness and large shifts in species composition may occur.